Employee Training in the Federal Service Fiscal Year 1970. - Civil Service Commission, Washington, DC. Bureau of Training; Civil Service Commission, Washington, DC. Bureau of Training ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This fourth annual review of employee training activities throughout the Federal Service is derived from information provided by agencies in their annual training reports to the Civil Service Commission for fiscal year 1970. Major sections of the report are: (1) Progress Toward Significant Training Goals, (2) Agency Training Activities, (3) Accomplishments Through Training, (4) Activities of the Civil Service Commission, and (5) Statistical Review of Training. Summary data from previous reports are included to make comparisons and show trends. Statistical tables and figures present the data. (JS)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (CS 1.48:T-7-A, $.75).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agencies; Costs; Employment Opportunities; Federal Government; Job Training; Occupational Mobility; Program Evaluation; Training Objectives; Vocational Education